KONTRIBUSI KELINCAHAN DAN KESEIMBANGAN TERHADAP KEMAMPUAN MENGGIRING BOLA - Sonyman Jaya; Andi Atssam Mappanyukki; Ichsani Ichsani; Nur Indah Atifah Anwar (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
This research is a research using descriptive analysis method with a quantitative approach which aims to determine whether there is a contribution of agility and balance to the ability to dribble the ball in players SSB Sheikh Yusuf. The independent variables in this study are agility and balance, while the dependent variable is the ability to dribble. The population in this study were all SSB Syekh Yusuf athletes, totaling 30 people. The data from this study were obtained through measurement test activities for each variable. The measurement of agility ability is by Agility Run , while the measurement of balance ability is using the Modified Bass Test Of Dynamic Balance and the measurement of dribbling skills is by Zig-Zag Dribbling . The results of the statistical analysis test on the contribution of agility to the ability to dribbling the ball on SSB Syekh Yusuf players obtained a significance value of 0.000 or p <0.05. This means that there is a contribution between the agility of SSB Syekh Yusuf players on the ability to dribbling the ball. Meanwhile, in the results of the statistical analysis test, the contribution of the balance data to the ball dribbling ability of the SSB Syekh Yusuf player obtained a significance value of 0.561 or p> 0.05. This means that there is no contribution between the balance of SSB Syekh Yusuf players on the ability to dribbling the ball. However, in the regression test between agility and balance variables on the dribbling ability of SSB Syekh Yusuf players, a significance value of 0.000 or p <0.05 was obtained. So it can be concluded that there is a significant relationship between agility and balance variables on the dribbling ability of SSB Syekh Yusuf players in a regression (together). Apart from that, the contribution value between variables in regression was found to have a positive contribution of 0.685 or at a very strong degree of contribution relationship.